Considerações sobre a utilização de pavimentos intertravados e betuminosos em áreas urbanas - Carvalho, Denise Barroso Andrade (2010)
The reality of pavement in médium and small brazilian cities is the execution of urban roads devoid of study, planning and sizing. This situation occurres a less useful life, a big maintenance cost and a big environmental degradation. Concerning this situation, allied the fact of the financial resources are usually insufficient since there is also the necessity of improvement in other social areas like basic sanitation, health and education, this work searches to establish guideline to help minicipal administrations to choose better the type of pavement to be used, concerning the trafficability, environmental and economic aspects. It is still imperative, it notes the cost of new ambiental requirement in the execution of paviments generating main for production process, and for taxes quarterly collected for the public organ. This study contemplates the interlocked and bituminous (bituminous hot machined concrete) pavements. It is presented a study of case in Passos city, Minas Gerais, searching to do a comparative analysis of these two types of pavements accomplishment. The result permited to collect an extense group of variables that can be used for definition of economic, tafficability and environmental aspects. It also permited a satisfatory evaluation of choosed methods for comparative analysis done by case study.